2019
DOI: 10.1186/s12955-019-1161-6
|View full text |Cite
|
Sign up to set email alerts
|

Coping with age-related hearing loss: patient-caregiver dyad effects on quality of life

Abstract: Background and aims Patients with age -related hearing loss (ARHL) and their natural caregivers have to confront a disability that produces progressive lifestyle changes. There is an interest in studying the ability of patients and their caregivers to cope with the difficulties that affect quality of life (QoL). In a sample of patient-caregiver dyads in the specific context of ARHL, we examine whether the QoL of patients and caregivers is influenced by the coping processes they use from a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Individual variation in QoL may be constructed from personality traits, i.e., neuroticism and choice of coping. These factors may account for some of the QoL variation seen in different respondent groups [ 27 ], including persons with HL [ 28 ]. We suggest that an axis of causality, from personality, via the choice of coping to hearing disability may be present in persons with hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Individual variation in QoL may be constructed from personality traits, i.e., neuroticism and choice of coping. These factors may account for some of the QoL variation seen in different respondent groups [ 27 ], including persons with HL [ 28 ]. We suggest that an axis of causality, from personality, via the choice of coping to hearing disability may be present in persons with hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the dispositional coping of patients and family caregivers was positively associated with the PTG of patients. A study by Lazzarotto et al (2019) in other patient populations also found that family caregivers’ coping styles affected the physical and psychological health of patients with age-related hearing loss. The possible reason may be that patient–caregiver dyads who know each other well and who encounter the same problems are inclined to cope with it in similar ways, and ultimately affected each other’s outcome (Lazzarotto et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Coping strategies, which dyads use, seem to be directly related with QoL of the PHI and their partners. Targeted interventions are proposed to help PHI and their partners to implement more effective coping strategies (Blazer and Tucci, 2019 ; Lazzarotto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%